Biomechanical and Histological Assessment of a Polyethylene Terephthalate Screw Retention Technology in an Ovine Metatarsal Fracture Model - Easley, Jeremiah; Puttlitz, Christian; Broomfield, Cecily; Palmer, Ross; Jones, Alexander; McGilvray, Kirk C. (Veterinary and Comparative Orthopaedics and Traumatology, 2020)
Objective Screw loosening in fracture fixation poses a clinical risk which may lead to implant failure, particularly in poor bone quality. The objective of this study was to examine the effectiveness of a novel screw retention technology (SRT) for increased screw purchase in a large animal metatarsal fracture model.Study Design This was a biomechanical, radiographic, and histological study utilizing an ovine metatarsal fracture model. Twenty-four sheep metatarsi underwent 3-mm ostectomies and were repaired with a nine-hole plate and 3.5-mm screws placed in oversized 3.5-mm holes to simulate worst case revision surgeries (i.e. no initial screw thread bone contact). Sheep were sacrificed at 3, 6 or 12 weeks (n = 6 each) post-operation. Post-sacrifice, each surgically implanted screw underwent either destructive mechanical testing or histomorphometric analyses.Results Treated metatarsi showed improved screw retention and normal fracture healing. Significant improvement in breakout strength and pullout strength of screws treated with the SRT were found as a function of healing time. Histologically, bone ingrowth at the screw interface was also shown to significantly increase with healing time. Improvements in fracture healing, indicated by an increase in bone fraction and decrease in void space at the osteotomy, were also observed with healing time.Conclusion The results demonstrate the effectiveness of the SRT as a method for improved screw retention in a rescue-screw type scenario.
Keywords: screw loosening; screw failure; fracture healing; ovine; screw retention